Borrowing Agreement Between Deutsche Bundesbank and the International Monetary Fund. (Policy Papers; Policy Paper ;, 2009)
In light of the multilateral effort to ensure the adequacy of the financial resources available to the International Monetary Fund, and with a view to supporting the Fund's ability to provide timely and effective balance of payments assistance to its members, Deutsche Bundesbank agrees to lend to the Fund an SDR-denominated amount up to the equivalent of EUR 15 billion.